Occupational history and genetic N-acetyltransferase polymorphism of urothelial cancer patients in Leverkusen, Germany - Golka, Klaus; Prior, V; Blaszkewicz, Meinolf; Cascorbi, I; Schöps, W; Kierfeld, G; Roots, I; Bolt, HM (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVES ': 'The study was designed to realize possible shifts in the ratio of slow to fast acetylators within a group of 196 urothelial cancer patients in an area with earlier benzine production.' ' METHODS ': 'The subjects were interviewed for occupational and nonoccupational risk factors. The patients were phenotyped for N-acetyltransferase 2 (NAT2) by Grant's caffeine test. A subgroup of 54 patients was additionally genotyped for NAT2.' ' RESULTS ': 'The antimode in the NAT2 phenotyping with the caffeine test (AFMU:1X ratio) was 1.0, as evidenced by additional genotyping of the subgroup of 54 patients. The prevalence of slow acetylators in the entire group of bladder cancer patients was 55%, in accordance with published figures for European populations. In a subgroup of 40 patients with occupational histories as workers in chemical or rubber industries 65% were slow acetylators. In a further subgroup of 28 cases having specifically worked at chemical production sites of the local chemical industry, 68% were slow acetylators.' ' CONCLUSIONS ': 'In contrast to earlier studies, this study shows no increased prevalence of slow acetylators among urothelial cancer patients in comparison with the normal population. However, in subgroups of cases with a likelihood of past occupational contacts with aromatic amines, there was a trend towards a higher representation of slow acetylators. This finding is in accordance with observations of others that the percentage of slow acetylators in urothelial cancer patients is generally decreasing, possibly because the production of benzidine and benzidine-based dyes ceased in the early 1970s.
Keywords: acetylation phenotype; aromatic amines; bladder cancer